Importance of the substrate's surface evolution during the MOVPE growth of 2D-transition metal dichalcogenides. (8th January 2020) - Mo, Jiongjiong; El Kazzi, Salim; Mortelmans, Wouter; Mehta, Ankit Nalin; Sergeant, Stefanie; Smets, Quentin; Asselberghs, Inge; Huyghebaert, Cedric
Abstract: In this paper, we explore the impact of changing the growth conditions on the substrate surface during the metal-organic vapor phase epitaxy of 2D-transition metal dichalcogenides. We particularly study the growth of molybdenum disulfide (MoS2 ) on sapphire substrates at different temperatures. We show that a high temperature leads to a perfect epitaxial alignment of the MoS2 layer with respect to the sapphire substrate underneath, whereas a low temperature growth induces a 30° epitaxial alignment. This behavior is found to be related to the different sapphire top surface re-arrangement under H2 S environment at different growth temperatures. Structural analyses conducted on the different samples confirm an improved layer quality at high temperatures. MoS2 channel-based metal–oxide–semiconductor field-effect transistors are fabricated showing improved device performance with channel layers grown at high temperature.